China–Southeast Asian nontraditional security engagement: a soft power mode in Beijing’s regional diplomacy? - Gong, Lina (2022)
This special issue seeks to provide a comprehensive and in-depth study on nontraditional security (NTS) issues in China–Southeast Asia relations, which has so far remained an understudied topic in Asian regional a airs. rough this speci c angle, the project engages the debate on how China uses its expanding power resources to shape international and regional agendas, co-opt other countries, and induce cooperative behaviors. Specifically, it contributes to a better understanding of China’s current interactions with the Association of Southeast Asian Nations (ASEAN) and its ten member states on NTS issues amid increasing salience of NTS threats and heightened tensions arising from traditional security challenges such as territorial disputes and great power rivalry.